Fatigue characterization of binder with aging in two length scales: sand asphalt mortar and parallel plate binder film. (20th March 2020) - Kommidi, Santosh Reddy; Kim, Yong-Rak; de Rezende, Lilian Ribeiro
Highlights: Fatigue characterization of binder with aging was compared at two length scales. A realistic binder film thickness was attempted using Sand Asphalt Mortar (SAM). SAM fatigue tests can sensitively capture the influence of aging on binder fatigue. SAM fatigue tests can distintively capture progressive microcracking and macrocracking phases. Abstract: Fatigue-cracking resistance of asphaltic materials and flexible pavements is strongly related to the properties of the binder under aging and its interaction with aggregate particles, which are small-scale physical-mechanical characteristics of components. Currently, there are binder test methods including the AASHTO TP 101 that are widely used to evaluate fatigue characteristics of asphalt binder. Despite the scientific leap for predicting and characterizing binder fatigue behavior in pavements, there are opportunities to better mimic the true state of the binder subjected to fatigue loading in pavements. This study attempted fatigue damage characterization using sand asphalt mortar (SAM) specimens, which are anticipated to better represent the realistic geometry (such as micrometer thick film) of binder in mixtures than typical binder fatigue tests that use 2-mm thick parallel plate specimens, while testing repeatability-efficiency can still be met due to the use of standard Ottawa sands as a load carrier between binder films. Multiple fatigue-related tests (i.e., time sweep and amplitude sweep) were conducted on both 2-mm thick binder specimens and SAM specimens by varying the level of aging to investigate the effects of binder length scale and aging on fatigue cracking behavior. The laboratory procedure to fabricate SAM specimens was presented with the testing repeatability, which supports the validity of the method. It was observed from the fatigue testing results that SAM testing could capture the microcracking and macrocracking phases more distinctively and sensitively than conventional binder fatigue testing, particularly with the influence of aging. These test results and findings imply that the SAM can be considered a proper solid phase to evaluate the properties and damage characteristics of binders and mastics under various conditions.